1999
DOI: 10.5188/ijsmer.7.273
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation through Partial Oxidation of Hydrocarbons in Supercritical Water

Abstract: Catalytic hydrogenation of naphthalene and dibenzothiophene through a water gas shift reaction (CO +H20•¨CO2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Tetralin (NP) and Decalin (DL) were the main products. As in the DBT experiments, the rate of naphthalene hydrogenation in CO−SCW and in CO 2 −H 2 −SCW was higher than that in H 2 −SCW. , Similar results were obtained for the denitrogenation of carbazole, namely, a faster reaction in CO−SCW and CO 2 −H 2 −SCW than in H 2 −SCW at a lower water density, as shown in Figure . However, for this system, the suppression of the hydrogenation rate with increasing water density was observed, which suggests the need for a new catalyst suitable for the dense SCW hydrogenation.…”
Section: Resultssupporting
confidence: 78%
“…Tetralin (NP) and Decalin (DL) were the main products. As in the DBT experiments, the rate of naphthalene hydrogenation in CO−SCW and in CO 2 −H 2 −SCW was higher than that in H 2 −SCW. , Similar results were obtained for the denitrogenation of carbazole, namely, a faster reaction in CO−SCW and CO 2 −H 2 −SCW than in H 2 −SCW at a lower water density, as shown in Figure . However, for this system, the suppression of the hydrogenation rate with increasing water density was observed, which suggests the need for a new catalyst suitable for the dense SCW hydrogenation.…”
Section: Resultssupporting
confidence: 78%
“…Likely the reason for the rather high CO 2 and the low H 2 yields in our experiments is that the gasification is not complete after 15 min, which means that the hydrogen missing in the gas phase may be bonded in the organic compounds of the liquid phase. Other studies show that H 2 formed via the water gas shift reaction can further react with organic compounds to form hydrogenated products .…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is catalyzed by metal, metal oxide or homogeneous catalyst and can be driven by removing one of the products. Studies by Arai et al [46,47] have demonstrated that hydrogenation reactions can be greatly accelerated in supercritical water (SCW) through the use of either direct introduction of carbon monoxide or in situ formation of CO through the partial oxidation of hydrocarbons. Experiments were conducted with NiMo/Al 2 O 3 at 673 K and 30-32 MPa, in various atmospheres (H 2 -SCW, CO-SCW, CO 2 -H 2 -SCW).…”
Section: Introductionmentioning
confidence: 99%